High risk human papillomavirus in the periodontium : A case control study - Anna Shipilova; Manjunath Mundoor Dayakar; Dinesh Gupta (Journal of Indian Society of Periodontology, 2017)
Background: Human papilloma viruses (HPVs) are small DNA viruses that have been identified in periodontal pocket as well as gingival sulcus. High risk HPVs are also associated with a subset of head and neck carcinomas. It is thought that the periodontium could be a reservoir for HPV. Aims: 1. Detection of Human Papilloma virus (HPV) in periodontal pocket as well as gingival of patients having localized chronic periodontitis and gingival sulcus of periodontally healthy subjects. 2. Quantitative estimation of E6 and E7 mRNA in subjects showing presence of HPV3. To assess whether periodontal pocket is a reservoir for HPV. Settings and Design: This case-control study included 30 subjects with localized chronic Periodontitis (cases) and 30 periodontally healthy subjects (controls). Two samples were taken from cases, one from periodontal pocket and one from gingival sulcus and one sample was taken from controls. Methods and Materials: Samples were collected in the form of pocket scrapings and gingival sulcus scrapings from cases and controls respectively. These samples were sent in storage media for identification and estimation of E6/E7 mRNA of HPV using in situ hybridization and flow cytometry. Statistical analysis: Statistical analysis was done by using, mean, percentage and Chi Square test. A statistical package SPSS version 13.0 was used to analyze the data. P value < 0.05 was considered as statistically significant. Results: pocket samples as well as sulcus samples for both cases and controls were found to contain HPV E6/E7 mRNAInterpretation and Conclusion: Presence of HPV E6/E7 mRNA in periodontium supports the hypothesis that periodontal tissues serve as a reservoir for latent HPV and there may be a synergy between oral cancer, periodontitis and HPV. However prospective studies are required to further explore this link.